TRANSFORMASI INDUSTRI KELAPA SAWIT: HILIRISASI BERKELANJUTAN MENGHADAPI DAYA SAING GLOBAL DAN EKONOMI HIJAU - Dwi Najah Tsirwiyati (Esensi Hukum, 2024)
The downstream processing of palm oil in Indonesia presents significant potential to support the national economy while mitigating environmental impacts. Palm oil is one of the key commodities contributing to Indonesia's exports and Gross Domestic Product (GDP). However, it is important to note that the expansion of palm oil plantations has contributed to deforestation, loss of biodiversity, and increased greenhouse gas emissions. The downstream processing of palm oil, which involves transforming this commodity into value-added products such as biodiesel, cosmetics, and food, has the potential to enhance Indonesia's competitiveness in the global market. Furthermore, downstream processing can create new job opportunities and strengthen the domestic industrial sector. However, to fully harness this potential, substantial investments, sustainable research and development, and supportive policies are required, particularly in managing the environmental impacts generated by this industry. Therefore, a sustainable downstream strategy is crucial to ensure that this sector not only provides long-term economic benefits but also reduces negative environmental impacts.